Comprehensive analysis of the circular RNA expression profile and circRNA–miRNA–mRNA network in the goat skin with divergent wool curvature - Yingxiao Su; Zhanqiang Zhao; Zhanfa Liu; Xiaobo Li; Qian Chen; Yabin Pu; Lin Jiang; Xiaohong He; Yuehui Ma; Qianjun Zhao (Animal Research and One Health)
Abstract Wool curvature is one of the most valuable characteristics of Zhongwei goat fur. As the goats grow, the curvature progressively diminishes, which has a substantial impact on the quality and market value of wool. Circular RNAs (circRNAs) are a class of noncoding RNA and play vital roles in animal growth and development. However, the expression and function of circRNAs in the wool curvature of Zhongwei goats are unclear. In our study, we conducted circRNA expression profiling of Zhongwei goat skin exhibiting divergent curvature wool phenotypes at two developmental stages using the RNA‐seq. In total, 12,682 circRNAs and 158 differentially expressed circRNAs (DE circRNAs) were identified. KEGG analysis illustrated that host genes of DE circRNAs were significantly enriched in the signaling pathways of Ras, JAK/STAT5, and cAMP, which might affect wool curvature. We further validated five circRNAs using qRT‐PCR, which were consistent with the sequencing results. Functional verification assay demonstrated that circRNA8782 regulated fibroblast proliferation. In addition, we constructed a regulatory competing endogenous RNA (ceRNA) network and predicted circRNA3173‐miR‐16b‐5p‐IGF1 axes involved in the regulation of wool curvature. Our result will provide the foundation for uncovering the regulatory mechanisms of underlying wool curvature patterns in goats.